Properties of invertible elements in complete intuitionistic fuzzy pseudo normed algebra - Bivas Dinda; Santanu Kumar Ghosh; Tapas Samanta (Journal of New Results in Science)
In this paper, we deal with the invertible elements in a complete intuitionistic fuzzy pseudo normed algebra (in short, IFPNA) with respect to Archimedean t-norm and Archimedean t-conorm. It is done by studying the continuity of algebraic operations in a complete IFPNA and investigating the condition for existence of inverse of an element in a complete IFPNA. Also some properties of invertible elements are studied. It is observed that the set of invertible elements in a complete IFPNA is an open set.